2009
DOI: 10.3102/0013189x08328876
|View full text |Cite
|
Sign up to set email alerts
|

Why Study the U.S. South? The Nexus of Race and Place in Investigating Black Student Achievement

Abstract: This article highlights the significance of the U.S. South in scholarly discussions regarding the academic achievement gap involving Black students. Despite national concern, patterns embedded in Black student achievement as related to geographical influences generally are ignored, especially in the South, where the majority of Black people in the United States reside. The authors refine the scholarship on the Black-White achievement gap through an analysis of racialized national spaces and population shifts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 68 publications
0
61
0
1
Order By: Relevance
“…Multiracial and African, Latino, Asian-Pacific Islander, and Native American students now constitute slightly more than half of all students attending public schools in 15 southern states. As the South continues to become a more diverse and urbanized region, scholars note that it has been a neglected site of investigation for Black student achievement (Morris & Monroe, 2009). Although the reasons for academic inequities and the achievement gap are complex, the increasing racial and ethnic diversity among students in K-12 schools and the accompanying decline in diversity among the population of teachers is certainly worth considering.…”
Section: Renewed Segregation In the Southmentioning
confidence: 99%
“…Multiracial and African, Latino, Asian-Pacific Islander, and Native American students now constitute slightly more than half of all students attending public schools in 15 southern states. As the South continues to become a more diverse and urbanized region, scholars note that it has been a neglected site of investigation for Black student achievement (Morris & Monroe, 2009). Although the reasons for academic inequities and the achievement gap are complex, the increasing racial and ethnic diversity among students in K-12 schools and the accompanying decline in diversity among the population of teachers is certainly worth considering.…”
Section: Renewed Segregation In the Southmentioning
confidence: 99%
“…Morris and Monroe (2009) argue that a major explanation for the low graduation rates of African Americans and others in the United States has to do with the cultural legacy born of slavery in the South. The authors demonstrate how and why the South is critical to understanding the educational achievement gap (see also Fitzpatrick and Yoel 1992).…”
Section: Educatementioning
confidence: 99%
“…They found that "although race looms large in southern understandings of daily life…family structure, maternal attributes, peers' skill levels, and rural and nonrural location" (p. 317) were the most salient factors in explaining variation in students' achievement in their particular study. They suggested that it is important for social workers to study and address issues of poverty and location when seeking to understand student achievement (see also Morris & Monroe, 2009). This finding underscores the impact of a student's geographic and social context on his or her experience in school.…”
Section: Geography and Social Contextsmentioning
confidence: 99%